Eficiencia de lámparas de rayos ultravioleta en la disminución de Coliformes Termotolerantes del efluente de la PTAR Lagunas de San José –Chiclayo - Roldán Fonseca, Katya Melissa (2019)
ABSTRACT The objective of this research is the efficiency of the 17 W, 25 W and 46 W ultraviolet lamps in the removal of thermotolerant coliforms from the effluent of the PTAR Lagunas San José, Chiclayo; As a study material, PVC cylinders of 120 L capacity for sample collection, UV lamp, sterilized glass bottles were used to determine the population of thermotolerant coliforms by the method of multiple dilutions and coolers at 4 ° C to be transported to the microbiological laboratory; with which it was obtained as results that the 46W UV lamp was highly efficient in the removal of coliforms and the combined use of the 5 μm and 1 μm filters in the experimental system allowed to obtain a high efficiency in the decrease of thermotolerant coliforms concluding that the higher the power of the UV lamp and the lower filtration process will be the population of thermotolerant coliforms.